Optimalisasi Layanan Harmony Wooden Villas Melalui Pelatihan English Writing dan Speaking Skill - Yogi Susana, Kadek; Kadek Agus Bisena, I; Ari Iswara, Agus (Green Publisher Indonesia, 2025)
Harmony Wooden Villas is a tourist accommodation where most of the guests come from abroad and use English in their communication so that the staff are expected to have good communication skills in English. However, initial observations showed a lack of knowledge and skills of staff in writing and speaking English which has an impact on the quality of service. To overcome this problem, community service activities by lecturers from Institut Bisnis dan Teknologi Indonesia (INSTIKI) were carried out with the aim of improving staff's English skills and optimizing villa services through writing and speaking skills training. The training used a face-to-face method with a lecture and discussion approach, as well as the use of technology to maximize learning effectiveness. Evaluation was carried out through initial and final training ability tests, as well as feedback from participants. The results showed a significant increase in communication skills, especially in composing written correspondence and interacting with customers in English. In addition, participants stated that the methods applied were effective and supported increased learning motivation. This activity is expected to provide a long-term contribution to the quality of service at Harmony Wooden Villas and become a model for developing human resource capacity in other hospitality sectors.